The mechanical behaviours of the Ti-10V-2Fe-3Al alloy under the high-temperature and dynamic loading conditions - Li Lintao; Zhang Xiaoying; Li Zhiqiang; Wang Zhihua; Ma Wei (EPJ Web of Conferences, 2018)
In this work, we develop a high-temperature dynamic testing technology for characterizing the properties of Ti-1023 alloy. The modified Hopkinson torsion bar system includes a high-temperature furnace subsystem and a water cooling subsystem. High-temperature dynamic tests of the alloy are performed. The dependence of the yield stress on the temperature and the shear strain rate is studied. The scanning electron microscopy observations show that the microstructural evolution makes up of two steps: the first one is caused by thermal loading and the second one by the mechanical loading. The high-temperature dynamic constitutive model is established based on the experimental results.